Marriage of convenience. 1 - Ken; Ken; Hanheun (Marriage of Convenience, 2025)
""Do you recall how much our marriage cost?"Countess Bianca de Arno was infamous throughout the land as a haughty, extravagant woman who spurned her spouse, neglected her duties, and spent her estate'smoney with wild abandon--in her first life, that is! After meeting a miserable and lonely end following the tragic death of her heroic husband, Bianca wakes up back in the castle as her nineteen-year-oldself. It's not exactly the second chance she'd prayed for, but she'll do anything to avoid the cold and hunger that plagued her before.In fact, she's even willing to make amends with the indifferent manshe calls her husband--but with an entire lifetime of misunderstandings between them, it'll take more than a few clumsy advances to winhim over!"--